Magnetic Field Imaging of Superparamagnetic Particles Using High‐Density, Perfectly Oriented NV Centers in Diamond CVD Film. Issue 22 (14th November 2018) - Hatano, Yuji; Sekiguchi, Takeharu; Iwasaki, Takayuki; Hatano, Mutsuko; Harada, Yoshie
Abstract : The spatial and temporal resolutions of bio‐imaging with magnetic nanoparticles (MNP) as a label and a diamond substrate as a magnetic field imager are investigated. To realize fast and accurate magnetic field imaging even for a substrate with unresolved hyperfine peaks, relative fluorescence is measured at four operation points corresponding to the steepest slopes of two dips in the ODMR spectrum. The (111) diamond substrate with a 3.5‐μm thick chemical vapor deposition film with an NV − density of 1.6 × 10 16 cm −3 allows us to detect 1‐μm MNPs scattered on its surface with an accumulated exposure time of 19 s under external DC magnetic field of 1.3 mT. Theoretical limit of temporal sensitivity is estimated to be more than four orders of magnitude smaller than measured. Although for measurement in culture medium, an objective lens with longer working distance is required and the condition will become somewhat worse, a spatiotemporal resolution of <1 s and <1 μm for the density and quality of the NV centers used in this study is expected if the already reported sensitivity enhancement technologies are further incorporated. Abstract : For NV centers in diamond, four‐frequency ODMR measurement scheme with feedback control enables to obtain clear magnetic field images, by compensating temporal fluctuation and spatial inhomogeneity to realize efficient accumulation of ODMR signals. The authors apply this scheme to magnetic field imaging of superparamagnetic nanoparticles on a CVD diamond film containing perfectly aligned NV centers.